2016
DOI: 10.1111/obr.12456
|View full text |Cite
|
Sign up to set email alerts
|

Waist‐to‐height ratio, body mass index and waist circumference for screening paediatric cardio‐metabolic risk factors: a meta‐analysis

Abstract: Waist-to-height ratio (WHtR) is superior to body mass index and waist circumference for measuring adult cardio-metabolic risk factors. However, there is no meta-analysis to evaluate its discriminatory power in children and adolescents. A meta-analysis was conducted using multiple databases, including Embase and Medline. Studies were included that utilized receiver-operating characteristics curve analysis and published area under the receiver-operating characteristics curves (AUC) for adiposity indicators with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
180
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(206 citation statements)
references
References 62 publications
15
180
1
10
Order By: Relevance
“…For assessment of obesity, only SDS-BMI was available and WC was not measured. In adults, WC has been suggested as a better predictor of cardiovascular disease and type 2 diabetes than BMI [48, 49], while in children the results comparing WC and BMI in regard to cardiometabolic risk are less clear [50, 51], and a recent meta-analysis of 30 studies found no significant advantage of WC over BMI in the prediction of cardiometabolic risk in children and adolescents [52]. …”
Section: Discussionmentioning
confidence: 99%
“…For assessment of obesity, only SDS-BMI was available and WC was not measured. In adults, WC has been suggested as a better predictor of cardiovascular disease and type 2 diabetes than BMI [48, 49], while in children the results comparing WC and BMI in regard to cardiometabolic risk are less clear [50, 51], and a recent meta-analysis of 30 studies found no significant advantage of WC over BMI in the prediction of cardiometabolic risk in children and adolescents [52]. …”
Section: Discussionmentioning
confidence: 99%
“…A good screening test should be not only highly predictive but also easy to perform and interpret [12]. BMI and WC have been the most commonly used predictors of obesity and cardiovascular disease to date.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, WHtR can be applied to a single reference point regardless of race, sex, or age. Consequently, it has been proposed as a population-based screening tool for cardiometabolic risk prediction in large-scale epidemiological studies and during medical examinations [12,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…The first systematic review to show that WHtR performed better than BMI in predicting cardiometabolic risk was published in 2008 [26]. Since then, other systematic reviews and meta-analyses have compared several anthropometric indices including WHtR with BMI and always found that WHtR was the best predictor of cardiometabolic risk in adults [27][28][29] and in children [30].…”
Section: Step1: Central Obesity Is Harmfulmentioning
confidence: 99%